A Novel Design of MSM Photodetector and the Investigation of Two-Top Contacts Spacing Effects on Detection Speed and Transient Response - Savarimuthu Robinson; Yunjian Jia (Advances in Engineering and Intelligence Systems)
The photodetector is one of the main components of the optical communication systems that converts optical signal to electrical signal. Metal Semiconductor Metal photodetector is one type of photodetector with a high coefficient of quantum efficiency and high speed while having a simple structure. In this paper, a novel microstructure of the Metal Semiconductor Metal photodetector consisting of an absorbing layer of semiconductor and two metal electrodes which act as two back-to-back Schottky diodes is designed and simulated. Incident light is absorbed by the active area between the two top electrodes and generates electron-hole pairs which are collected by electrodes and then an electric current is generated. Therefore, by determining the transient response of the detector for the various distance between the electrodes, we can find out the effect of the distance on the detection speed and detector response. In the best case, the response rate is 57 ps and the maximum instantaneous current is 3.27 nA. The shorter the distance between the two upper detector electrodes, called the empty area, the faster the detection speed increases, and the total light current decreases due to the reduction of the light flux descending on the surface.